Isolation and screening of indigenous microalgae species for domestic and livestock wastewater treatment, biodiesel production, and carbon sequestration. (15th September 2022) - Lee, Jae-Cheol; Joo, Jae-Hyoung; Chun, Byung Hee; Moon, Kira; Song, Seung Hui; Kim, Yun Ji; Lee, Sung Moon; Lee, Aslan Hwanhwi
Abstract: The use of indigenous microalgae strains for locally generated domestic (DWW) and livestock wastewater (LWW) treatment is essential for effective and economical applications. Phototrophic microalgae-based biofuel production also contributes to carbon sequestration via CO2 fixation. However, simultaneous consideration of both isolation and screening procedures for locally collected indigenous microalgae strains is not common in the literature. We aimed to isolate indigenous microalgae strains from locally collected samples on coastlines and islands in South Korea. Among five isolated strains, Chlorella sorokiniana JD1-1 was selected for DWW and LWW treatment due to its ability to grow in waste resources. This strain showed a higher specific growth rate in DWW than artificial growth medium (BG-11) with a range of 0.137–0.154 d −1 . During cultivation, 96.5%–97.1% of total nitrogen in DWW and 89.2% in LWW was removed. Over 99% of total phosphorus in DWW and 96.4% in LWW was also removed. Finally, isolated C. sorokiniana JD1-1 was able to fix CO2 within a range of 0.0646–0.1043 g CO2 L −1  d −1 . These results support the domestic applications of carbon sequestration–efficient microalgae in the waste-to-energy nexus. Highlights: Indigenous microalgae species was isolated from island and coast in Korea. Selected microalgae strain showed a better performance in waste sources than artificial medium. Nutrients in domestic and livestock wastewater were assimilated during microalgae cultivation. Isolated Chlorella sorokiniana JD1-1 has the capacity to fix CO2 about 0.0646–0.1043 g CO2 L −1 D −1 . Sustainable waste-to-energy strategy was suggested using indigenous bioresources.